Hubungan Pengetahuan dengan Sikap Mengenai Implementasi Teknologi Wolbachia-Aedes pada Tenaga Kesehatan Kota Cirebon - Tajudin Tajudin; Muhammad Hussein G; Witri Pratiwi (Universitas Pahlawan Tuanku Tambusai, 2026)
Dengue Hemorrhagic Fever remains a public health problem, particularly in endemic areas of Indonesia where cases continue to increase. Wolbachia-Aedes technology is an innovative vector control strategy with the potential to reduce dengue virus transmission. Healthcare workers play an important role in educating the community and supporting public acceptance of this intervention. This study aimed to determine the relationship between knowledge and attitudes regarding the implementation of Wolbachia-Aedes technology among healthcare workers in Cirebon City. Methods: This was an analytical observational study with a cross-sectional design. The population consisted of healthcare workers at public health centers in Cirebon City, with 126 respondents selected using cluster random sampling. The independent variable was knowledge, while the dependent variable was attitude toward the implementation of Wolbachia-Aedes technology. Data were collected using a validated and reliable questionnaire. Univariate and bivariate analyses were performed, and the Chi-square test was used to assess the relationship between variables. Results: Most respondents had good knowledge, totaling 100 respondents (79.4%), and 76 respondents (60.3%) showed a positive attitude. Bivariate analysis showed a significant relationship between knowledge and attitudes regarding the implementation of Wolbachia-Aedes technology, with p=0.0001 and PR=14.143. Conclusion: Knowledge was significantly associated with healthcare workers’ attitudes toward the implementation of Wolbachia-Aedes technology in Cirebon City. Healthcare workers with better knowledge tended to have more positive attitudes toward the implementation of Wolbachia-Aedes technology.